UJI AKTIVITAS ANTI INFLAMASI EKSTRAK ETANOL BAWANG MERAH (Allium Cepa L.) VARIETAS BIMA BREBES PADA TIKUS PUTIH JANTAN GALUR WISTAR - Abidia Kamil; Adita Silvia; Rani Prabandari (Jurnal Farmasi & Sains Indonesia, 2022)
Shallots are one of the leading vegetable commodities in Indonesia. The center for shallot production is Central Java Province, especially in the Brebes Regency area. Shallots (Allium cepa L) can be used as medicine, one of which is as an anti-inflammatory. The purpose of this study was to determine the anti-inflammatory activity and to determine the best dose of ethanolic extract of shallot (Allium cepa L) which has anti-inflammatory activity against male white rats of wistar strain. The method used is the experimental method. Shallot extract (Allium cepa L.) was extracted using 70% ethanol by maceration method. The test animals used were white male rats wistar strain as many as 25 rats weighing 200-250 grams. The test animals were divided into 5 groups, namely the negative control group (Na CMC 0.5%), the positive group (Na Diclofenac), the onion extract dose variation group (25 mg/KgBW, 50 mg/KgBW, and 100 mg/KgBW). . Treatment 1 hour afterthe hind legs of rats was induced by subplantar carrageenin. The measurement of the volume of edema on the soles of the rats' feet was observed once every 1 hour for 6 hours. The results of the study showed that there was antiinflammatory activity at the three doses (25 mg/KgBW, 50 mg/KgBW and 100 mg/KgBW) ethanol extract of shallot (Allium cepa L) Bima Brebes in male white rats of the Wistar strain. The best dose of ethanolic extract of shallot (Allium cepa L) which has anti-inflammatory activity against male white rats of wistar strain is 50 mg/KgBW.